Body Armor, Performance, and Physiology During Repeated High-Intensity Work Tasks. - Larsen, B.; Netto, Kevin; Skovli, D.; Vincs, K.; Vu, S.; Aisbett, B. (Association of Military Surgeons of the U S, 2012)
This study examined the effect of body armor during repeated, intermittent high-intensity simulated military work. Twelve males performed 11 repetitions of a military style circuit, wearing no armor on one occasion and full armor (~17 kg) on another. Performance was measured by the time to complete individual work tasks plus overall circuit time to completion. Heart rate, intestinal temperature, and rating of perceived exertion were recorded after each circuit. Participants’ circuit time to completion was 7.3 ± 1.0 seconds slower (p <0.01) when wearing armor. Shooting, vaulting, and crawling were also slower (0.8 ± 0.2, 0.4 ± 0.2, and 1.0 ± 0.4 seconds, respectively; all p ≤ 0.05). No differences were observed for box lifting. Higher core temperatures were reported for the armor condition for circuit’s 7 to 11 (p = 0.01–0.05). Rating of perceived exertion was higher (1 ± 0; p = 0.03) when wearing armor. No differences were observed for heart rate. Wearing armor impairs repeated high-intensity military task performance. In the relatively short work time utilized, this decrement did not accrue over time. The impairment may, then, be related to the armor load, rather than accumulating fatigue.